Non-ferroelectric relaxor properties of BMN, Bi3.55Mg1.78Nb2.67O13.78 pyrochlore - Tan, Phei Yi; Tan, Kar Ban; Khaw, Chwin Chieh; Zainal, Zulkarnain; Chen, Soo Kien; Lee, Oon Jew; Chon, Mun Ping (Elsevier, 2020)
Phase-pure Bi3.55Mg1.78Nb2.67O13.78, BMN pyrochlore was prepared by conventional solid-state reaction at 1025 °C for 2–3 days. Electrical properties measured by impedance spectroscopy over the range 10–1073 K showed relaxor behaviour with a maximum dielectric constant, ε′max of 209 at its temperature maximum, Tmax of 204 K. Impedance data were analysed by fixed-frequency sweeps of dielectric constant and tan δ and variable frequency scans at fixed temperature. Low temperature data were modelled using the classic dielectric relaxation circuit that consists of a resistance in combination with series and parallel capacitances, but modified to include a constant phase element that introduced variable resistances and capacitances into the equivalent circuit. There was no evidence of ferroelectric behaviour, either from extrapolation of high temperature Curie-Weiss plots or the temperature-dependence of low temperature capacitance data. At intermediate temperatures, ∼240–623 K, BMN is an insulator with resistivity >10 MΩ cm. Above ∼623 K, it is a modest electrical conductor, activation energy 1.07 eV; the charge carriers are probably oxide ions.